Management of venomous snakebites in dogs and cats in Brazil - Ferreira Júnior,R.S. (2004)
Snake envenoming is a major problem both to veterinary and human medicine in tropical countries due to high incidence, severity, and sequelae. In Brazil, most envenomings involving animals are caused by Bothrops and Crotalus snakes; these are the highest risk to animals. This study reports on Bothrops and Crotalus envenomings in dogs, the main species responsible for epidemiology, pathogenesis, venom action, clinical signs, sequelae and complications, clinical pathology, necropsy findings, diagnosis, and treatment. Veterinarians must be capable of identifying the snake not only by observing its characteristics but also symptom evolution.